Migration characteristics of metal contaminants through a peat soil - Ahmad, Kamarudin; Aris, Azmi (Faculty of Civil Engineering, 2009)
Migration of contaminants from illegal dumping of industrial wastes has the potential to give rise to problem of groundwater pollution. Thus, a study involving adsorption batch tests and leachability column tests were performed to determine the effects of soil acidity on potential of leachability of metal contaminants. Two different types of soil were utilized in this study, namely acid sulphate soil and peat soil obtained from Parit Ngamarto in Batu Pahat and Kampung Parit Mansor Benut in Pontian, respectively. In addition to chemical tests, basic engineering tests to determine the engineering properties were also undertaken. Three types of metal namely copper (Cu), aluminium (Al) and lead (Pb) were utilized as metal contaminants. It was found from this study that both acid sulphate and peat soil have low permeability, 6 x 10-6 m/s and 2 x 10-6 m/s, respectively. This study also shows that the acid sulphate and peat soils have certain adsorption capacity towards Cu, Al and Pb. The adsorption capacity of peat soil is higher than that of acid sulphate soil. In addition, acidity from acid sulphate and peat soils contribute to the leaching of the metals. Acid sulphate soil generated higher acidity than peat soil, hence, causing higher concentration of metals being leached out. The effect of the acidity is higher for Al as compared to Cu.